Identification and Reuse of Patrimony in the Process of Reinventing Cities: a reflection from the city of Almada - Bezerra, Roselane Gomes (2016)
The city of Almada, in Portugal, reaches the XXI century as a post-industrial city, with buildings in ruins, degraded spaces and abandoned facilities for the shipbuilding industry. However, signs of degradation became amenable to conversion through “rehabilitation” projects. Starting from the observation of discourses of architects and managers in Participation Forums, the purpose of this article is to present an analysis of the idea of “qualification” of uses in the city, under the projects of urban intervention. The paper shows how the concept of “turning into patrimony in order to qualify spaces and people’s lives,” common to diverse narratives of intervention plans, is indicative of a “disputing urbanity” and gives clues to broaden the debate on urban policies and the process of reinvention of contemporary cities.